A nationwide, multicenter retrospective study on the effectiveness and safety of eribulin in Korean breast cancer patients (REMARK). (December 2020) - Park, Min Ho; Lee, Soo Jung; Noh, Woo Chul; Jeon, Chang Wan; Lee, Seok Won; Son, Gil Soo; Moon, Byung-In; Lee, Jin Sun; Kang, Sung Soo; Suh, Young Jin; Gwak, Geumhee; Kim, Tae Hyun; et al.
Abstract: Purpose: Approval of eribulin for metastatic breast cancer was based on data primarily from Western patients, and there is a paucity of data on the effectiveness and safety of eribulin for Asian patients. To determine the effectiveness and safety of eribulin in Korean women with breast cancer in a real-world setting, we conducted a nationwide, multicenter, retrospective study. Methods: Patients with locally advanced or metastatic breast cancer who were treated with eribulin in 14 centers throughout Korea were included in this study. Eribulin was generally administered at a dose of 1.23 mg/m 2 (equivalent to 1.4 mg/m 2 eribulin mesylate) by intravenous infusion for 2–5 min, or as a diluted solution, on Days 1 and 8 of every 21-day cycle. The primary endpoint was progression-free survival (PFS) rate at 6 months. Secondary endpoints included median PFS, overall survival (OS), time-to-treatment failure (TTF), tumor response rate, and incidence of hematologic treatment-emergent adverse events (TEAEs). Results: The safety and full analysis populations included 398 and 360 (38 had no efficacy data) patients, respectively. The PFS rate at 6 months was 37.8%. Median PFS, OS, and TTF were 134, 631, and 120 days, respectively. Objective response rate, clinical benefit rate, and disease control rate were 18.1%, 50.6%, and 49.4%, respectively. Hematologic TEAEs were reported in 65.1% of patients; neutropenia (56.8%) and anemia (11.3%) were most common. Conclusion: Real-world effectiveness and safety of eribulin in Korean breast cancer patients were consistent with previous reports; no new safety concerns were identified. Graphical abstract: Image 1 Highlights: Metastatic breast cancer patients were treated with eribulin (1.23 mg/m 2, IV). Progression-free survival rate at 6 months was 37.8% in eribulin-treated patients. Median progression-free and overall survivals were 134 and 631 days, respectively. Hematologic treatment-emergent adverse events were reported in 65.1% of patients. Effectiveness and safety of eribulin were consistent with previous reports.